Coherency Identification in Interconnected Power Systems - An Independent Component Analysis Approach - Ariff,MAM; Pal,BC (IEEE Transactions on Power Systems, 2013)
This paper presents a novel approach to the coherency identification technique in interconnected power system using independent component analysis (ICA). The ICA is applied to the generator speed and bus angle data to identify the coherent areas of the system. The results of the application of ICA using simulated data from 16-machine 68-bus system model and on data gathered through U.K. University-based Wide-Area Measurement System are presented. The approach is able to identify the cluster of generators and buses following a disturbance in the system. It is also demonstrated that the approach is robust in the presence of noise in measured signal, which is an important factor to be considered for assessing the effectiveness of any measurement-based technique.